Enhanced Antifungal and Wound Healing Efficacy of Statistically Optimized, Physicochemically Evaluated Econazole-Triamcinolone Loaded Silica Nanoparticles - Maheen, Safirah; Younis, Hina; Khan, Hafeez Ullah; Salman shafqat, Syed; Ali, Sajed; Rehman, Atta Ur; Ilyas, Saliha; Zafar, Muhammad Nadeem; Shafqat, Syed Rizwan; Kalam, Abul; Al-Ghamdi, Ahmed A. (Frontiers in Chemistry, 2022)
Co-encapsulated econazole nitrate-triamcinolone acetonide loaded biocompatible, physically stable, and non-irritating mesoporous silica nanoparticles (EN-TA loaded MSNs) were prepared and optimized by using Central Composite Rotatable Design (CCRD) for providing better therapeutic efficacy against commonly prevailed resistant fungal infections. These MSNs can significantly overcome the deficiencies and problems like short duration of action, requirement of frequent administration, erythema, burning sensation and irritation associated with conventional drug delivery systems. The stability of optimized MSNs prepared with 100 gm of oil at pH 5.6 with stirring time of 2 hours was confirmed from zeta potential value of -25 mV. The remarkable compatibility of formulation ingredients was depicted by X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR) spectra while scanning electron microscopy (SEM) and size analysis represented a very fine size distribution of nanoparticles ranging from 450-600 nm. The CCRD clearly predicted that the optimized parameters of MSNs have better values of percentage yield (85%), EN release (68%) and TA release (70%). As compared to pure drugs, the decreased cytotoxicity of EN-TA loaded MSNs was quite evident because they showed cell survival rate of 90% while in case of pure drugs, survival rate was 85%. During invivo antifungal testing against candida albicans performed on three different groups each consisting of 6 rabbits, the EN-TA loaded MSNs were relatively superior in eradicating the fungal infection, as a single animal showed a positive culture test. Rapid recovery of fungal infection and a better therapeutic effect of EN-TA loaded MSN were quite evident in wound healing and histopathology studies. Likewise on 14th day, a larger inhibitory zone was measured for optimized nanoparticles (15.90 mm) compared to the suspension of pure drugs (13.90 mm). In skin irritation studies, MSNs did not show a grade of erythema compared to pure drugs, which showed a four-fold grade erythema. As a result, MSNs loaded with combination therapy seems to have a potential of improving patient compliance and tolerability by providing enhanced synergistic anti-fungal effectiveness at a reduced dose with accelerated wound healing and reduce toxicity of therapeutics.